Intervensi Sosial Sebagai Strategi Komunikasi Dalam Menurunkan Stunting di Sidoarjo Jawa Timur - Masya, Herna; Salim Alatas (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2024)
The stunting rate decreased by 2.8%, which was 21.6% in 2022 compared to 24.4% in 2021. The decline is a positive development, but it is still above the threshold set by the World Health Organization (WHO) which should not exceed 20%. This shows that the problem of stunting in Indonesia still requires serious attention. The purpose of the study was to understand social intervention as one of the communication strategies in reducing stunting rates in Sidoarjo Regency. Interventions in communication for social and behavioral change include various methods such as interpersonal communication, the utilization of mass media, and community mobilization and its social aspects. Qualitative research approach with constructivism paradigm. The data collection method was an in-depth interview with 4 resource persons, namely a public relations officer of the Sidoarjo Regency Health Office and three mothers who were the target audience for reducing stunting rates. The results showed that efforts to reduce stunting were carried out through two social interventions, namely specific nutrition interventions to address direct causes and nutrition-sensitive interventions to address indirect causes. Social interventions are carried out in a convergent manner with an emphasis on handling the causes of nutritional problems. Social and behavioral change communication approaches are used to raise awareness about stunting so as to encourage pregnant women and stunted children to improve nutrition and behave healthily.